Resonance Frequency Readout Circuit for a 900 MHz SAW Device - Heng Liu; Chun Zhang; Zhaoyang Weng; Yanshu Guo; Zhihua Wang (Sensors, 2017)
A monolithic resonance frequency readout circuit with high resolution and short measurement time is presented for a 900 MHz RF surface acoustic wave (SAW) sensor. The readout circuit is composed of a fractional-N phase-locked loop (PLL) as the stimulus source to the SAW device and a phase-based resonance frequency detecting circuit using successive approximation (SAR). A new resonance frequency searching strategy has been proposed based on the fact that the SAW device phase-frequency response crosses zero monotonically around the resonance frequency. A dedicated instant phase difference detecting circuit is adopted to facilitate the fast SAR operation for resonance frequency searching. The readout circuit has been implemented in 180 nm CMOS technology with a core area of 3.24 mm2. In the experiment, it works with a 900 MHz SAW resonator with a quality factor of Q = 130. Experimental results show that the readout circuit consumes 7 mW power from 1.6 V supply. The frequency resolution is 733 Hz, and the relative accuracy is 0.82 ppm, and it takes 0.48 ms to complete one measurement. Compared to the previous results in the literature, this work has achieved the shortest measurement time with a trade-off between measurement accuracy and measurement time.